Le tutorat – un dispositif d’aide à la réussite dans le contexte universitaire - Sujecka-Zając, Jolanta (Neofilolog, 2022)
Tutoring means personalized cognitive, metacognitive and affective support of the individual to better guide him/her on the path of learning or teaching. It seems to be experiencing a revival of interest in this difficultperiod of the pandemic where education is increasingly conflicting between face-to-face and distance learning. Tutoring is considered to be one of the most powerful devices for helping students succeed, but we propose to show its benefits also for teacher-researchers in the pedagogical aspect of their work. Our objective will be to synthesize the French and Anglo-Saxon experience that have long explored the positive impact of tutoring in the university context as well as to examine the conditions for its implementation in university courses in Poland. Our experience as a tutor of university teachers - although not yet very rich - will allow us to analyze some concrete cases.